The hidden economic and environmental costs of antimicrobial therapies: a call to action - Mildred Nelson; Sarah B. Green; Sujit Suchindran; Lucy S. Witt (Antimicrobial Stewardship & Healthcare Epidemiology)
The overuse and inappropriate use of antimicrobials have led to environmental waste and drug shortages. This challenges the ecological and economical sustainability of our healthcare system and worsens antimicrobial resistance.